ANALYSIS OF STAR DELTA STARTING WITH PLC BASED ON HUMAN MACHINE INTERFACE AGAINST STARTING CURRENT - Zidan, M. Zidan Alfariki; Mubarok, Rizky; Adzin Murdiantoro, Randi (Journal of Electronic and Electrical Power Applications, 2024)
This research is motivated by the observation that several industries still use manual control circuits, such as star delta controllers on 3-phase motors. So the author will conduct a study on the effect of using a star delta system with a manual circuit and PLC on a 3-phase electric motor with a capacity of 7.5 kW. The purpose of this study is to determine the stability of the initial current of the electric motor in the starting process, the current between the PLC and manual circuits and also to determine the occurrence of overshoot. PLC makes it easier to operate if the hardware and control room are 20 m apart, namely by using HMI (Human Machine Interface) to monitor the circuit. The data collection method is by observing the star delta PLC and manual circuits on 3-phase electric motors. The results of this study are that the star delta PLC control circuit produces a stable starting current surge of 21.11 - 22.37 A. Meanwhile, the manual star delta system has a starting current surge of 22.01 - 23.53 A. The current value on the star side measurement between the PLC and manual is 4 amperes - 5 amperes, while the star current value is calculated at 4.75 A without load. At the delta value produces a larger current because it uses a line-to-line voltage of 8.24 A without load. In the use of the circuit between PLC and manual there is no overshoot or voltage drop.